Ups-and-downs of Mediterranean terraced landscapes: comparative study of four cases in different countries - Barata, Filipe Themudo (2013)
Beyond politic decisions, landscape changes mostly result from the economic perception that each community has of its own territory and from the social practices related with agriculture and technical knowledge. Among the cultural landscapes with heritage value, the terraced ones are common in Mediterranean area. Terraces are used by people, or not, in reply to challenges arisen from economic, social and political alterations. In fact, the understanding of these challenges makes communities abandon or recover their terrace landscapes, although other factors as climate disruptions can affect them irremediably. Four terraced landscapes representative of the mentioned factors, and settled in different Mediterranean countries, are compared in this study. They are the following ones: - Safi (Morocco) This landscape is suffering a decay process accompanied by a land demographic decline. As most terraced fields are traditionally hand cultivated or ploughed by draught animals, they are progressively abandoned in benefit of mechanized fields. Actually, the increasing mechanization is one of the factors which contributes to the human desertification and thus affects drastically the preservation of the walls terraces since continuous hand maintenance is required; - Lebanon Mountain (Lebanon) The regional conflicts lead to population movements and this often causes land occupation changes. Many people who have taken refuge in this hilly region use their ancestral technical knowledge in building and maintaining field terraces for arable land. It is the only way they can cultivate and survive. - Luberon Mountain (France) In this Regional Park of Provence, land terraces subsistence is the fruit of communities and public authorities interest in keeping high value heritage landscapes. Most of the fields are occupied by olive trees but vineyards and cherry trees can also be found. One example of the special attention given to the heritage development of this land system is the management project for museological purposes called Conservatoire des Terrasses de Cultures, by the village of Goult. - Alto Douro (Portugal) As the upper Douro valley guarantees the selling and profit of the viticultural production, the pressure on the appropriation of land is huge. So the building of terraces was, and still is, the only way to increase the available cultivation area. In the meantime, and given its peculiar characteristics, this landscape has gained a great heritage value, recognized by UNESCO which classified it as World Heritage in 2001. On the other hand, the region has been highly developed in terms of tourism, which is indeed an important asset. Finally, it was thought over the different motivations which have led to the destruction of terraces, their recovery or the building of new ones, in the Mediterranean area.